Diagnostic Accuracy Of Lachman Test For Diagnosis Of Anterior Cruciate Ligament Tear In Adults With Knee Injuries Using Arthroscopy As Gold Standard - Danyal Ashraf; Muhammad Sheraz Mustafa; Sarmad Nasir Janjua; Shaheen Iqbal; Khurram Habib (Journal of Rawalpindi Medical College)
Abstract